KEMAMPUAN SISWA KELAS XI AKUTANSI 2 SMK NEGERI 3 PADANG MENULIS KARANGAN NARASI EKSPOSITORIS MENGGUNAKAN MEDIA GAMBAR BERSERI - Kasuma, Riska Sari; Nisja, Indriani; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
Teaching language skills in school aims to develop students language skills, one of which is a narrative essay expository writing skills using media beamed images that students are better motivated and able to find the idea for which was written based on what he observed in the glow images. This research is motivated by the following problem. First, the ability of students to write a narrative essay is still lacking. Second, the limited allocation of time to practice narrative writing skills that is 90 minutes. Third, the media used by teachers to teach writing narrative essay is less varied. Fourth, students interest in reading is still lacking. Fifth, students have difficulties when searching for ideas and develop ideas and put them in chronological order. Sixth, students difficult to distinguish between narrative expository essay with suggestive narrative essay. This study aimed to describe the ability of class XI students of Accounting 2 SMK Negeri 3 Padang writing narrative expository essay using media images beamed in terms of expanding knowledge, convey information chronologically, based on rational reasoning, using language that is informative with emphasis on the use of the words denotative meaningful. This research is quantitative using descriptive methods. Data analysis was performed with the following steps: (1) checking the data, (2) scoring, (3) treating the score value, (4) determine the arithmetic mean, (5) the ability to classify students by using a scale of 10, (6) make histogram based on the ability of students, (7) to analyze and discuss the results, (8) concludes the analysis. The results of data per indicators are as follows. (1) 1 indicator (expanding knowledge) is quite an average of 61.71, (2) 2 indicators (conveying information about an event in chronological order) quite well with an average of 86.85, (3) 3 indicators (essay based on rational reasoning) quite well with the average 85.14, (4) 4 indicators (using language that is informative with emphasis on the use of meaningful words denotative) quite well with an average of 84. Based on the results of the values obtained, it can be concluded that the ability of class XI students of Accounting 2 SMK Negeri 3 Padang writing narrative expository essay using media images beamed to the four indicators considered good with an average of 79.42.